TECHNOLOGY OF USING THREE-DIMENSIONAL MODELS OF LOCATION IN THE UNIFIED GEOINFORMATION ENVIRONMENT OF THE ARMED FORCES OF UKRAINE - Lytvynenko, Natalia; Korenets, Oleksandr (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
B a c k g r o u n d . The use of three-dimensional terrain modeling by commanders during their decision-making during the execution of assigned tasks will allow them to gain a tactical advantage on the battlefield. Given the current lack of a methodological foundation for justifying the methodology of constructing three-dimensional terrain models for use in the geoinformation subsystems of the Automated Control System of the Armed Forces of Ukraine (ACS AFU), as well as the practical absence of a modern information system for storing and publishing such data, the research objective is the development of a technology for using three-dimensional terrain models with modern geoinformation technologies to enhance decision-making efficiency during planning and the execution of tasks by military units.M e t h o d s . We employed methods such as analysis of scientific and reference literature on the research problem to determine its relevance, systematization, and generalization of scientific information, as well as a systemic analysis of current guidelines for creating and using three-dimensional terrain models in the development of technology for the placement and utilization of three-dimensional models on a geospatial portal.R e s u l t s . Considering the experiences of leading countries worldwide, contemporary approaches to organizing spatial monitoring systems, geospatial modeling tasks, and the diverse requirements posed on various components when creating a unified information space, the use of threedimensional terrain models is justified to enhance the efficiency of task execution by units of the Armed Forces of Ukraine. In the military sphere, three-dimensional terrain models can be applied to improve the computational tasks of artillery units, visualize defense and offensive operations, conduct combat actions in urban areas (3D modeling of buildings and structures), and create special maps with pseudo-three-dimensional representations of terrain forms, and more.C o n c l u s i o n s . The technology proposed in this work for the placement and use of three-dimensional models can be applied in the process of information filling for the components of the geospatial portal of the Armed Forces of Ukraine.
Keywords: three-dimensional terrain models, geospatial support of troops (forces), digital map, electronic map, geospatial portal, unified geoinformation environment, Armed Forces of Ukraine